2013
DOI: 10.5588/ijtld.12.0695
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of dormancy-related antigens in individuals infected with Mycobacterium tuberculosis in Japan

Abstract: T-cell responses to six antigens might contribute to natural protection against dormant M. tuberculosis. These antigens are therefore considered to be potential targets of novel vaccines to control M. tuberculosis reactivation in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 0 publications
0
27
1
Order By: Relevance
“…Thus, our observations may suggest that mono-and bifunctional CD4 ϩ and CD8 ϩ T cells producing IFN-␥ and/or TNF-␣ can contribute to effective mycobacterial growth control in individuals with LTBI (34, 48,64). Although in other studies higher frequencies of mono-and bifunctional CD4 ϩ T cells producing IFN-␥ and/or TNF-␣ in response to RD1 were found in PTB, compared to LTBI (18,19,27,28), the difference in the lengths of the in vitro cultures might explain this difference. Short-term cultures (24 h) have been mainly associated with the detection of a T cell effector memory phenotype, while long-term cultures (5 to 7 days), as used in this study, have been mainly associated with the detection of a T central memory phenotype (25,36,56,57,64).…”
Section: Fig 6 Memory Phenotypes Of Bifunctional Ifn-␥mentioning
confidence: 40%
See 3 more Smart Citations
“…Thus, our observations may suggest that mono-and bifunctional CD4 ϩ and CD8 ϩ T cells producing IFN-␥ and/or TNF-␣ can contribute to effective mycobacterial growth control in individuals with LTBI (34, 48,64). Although in other studies higher frequencies of mono-and bifunctional CD4 ϩ T cells producing IFN-␥ and/or TNF-␣ in response to RD1 were found in PTB, compared to LTBI (18,19,27,28), the difference in the lengths of the in vitro cultures might explain this difference. Short-term cultures (24 h) have been mainly associated with the detection of a T cell effector memory phenotype, while long-term cultures (5 to 7 days), as used in this study, have been mainly associated with the detection of a T central memory phenotype (25,36,56,57,64).…”
Section: Fig 6 Memory Phenotypes Of Bifunctional Ifn-␥mentioning
confidence: 40%
“…Statistical differences between the groups were calculated with the Mann-Whitney U test. *, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. in response to in vitro stimulation with ESAT6 and CFP10; as discussed above, however, results have been inconclusive (15)(16)(17)(18)(19)(20).…”
Section: Conversely E6-c10mentioning
confidence: 99%
See 2 more Smart Citations
“…Transposon site hybridization mutation studies showed that Rv2004c is essential for the survival of Mtb in murine macrophages (23). The immunogenic potential of Rv2004c in latent tuberculosis infected (LTBI) individuals of Japanese population was reported (24). But, studies about humoral immune response in LTBI individuals from high burden countries such as India are lacking.…”
Section: Introductionmentioning
confidence: 99%